Al2O3/TiO2 inverse opals from electrosprayed self-assembled templates - Coll, Arnau; Bermejo, Sandra; Hernández, David; Castañer, Luís (Beilstein Journal of Nanotechnology, 2018)
The fabrication of high optical quality inverse opals is challenging, requiring large size, three-dimensional ordered layers of high dielectric constant ratio. In this article, alumina/TiO2–air inverse opals with a 98.2% reflectivity peak at 798 nm having an area of 2 cm2 and a thickness of 17 µm are achieved using a sacrificial self-assembled structure of large thickness, which was produced with minimum fabrication errors by means of an electrospray technique. Using alumina as the first supporting layer enables the deposition of TiO2 at a higher temperature, therefore providing better optical quality.
Keywords: electrospray; metamaterials; photonic crystals